The World-Creating COVID-19 Protest in Tel Aviv - Nestel, Anthony (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Anthony Nestel Title (English): The World-Creating COVID-19 Protest in Tel Aviv Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 158-161 Page Count: 4 Citation (English): Anthony Nestel, “The World-Creating COVID-19 Protest in Tel Aviv,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 158-161.